The Effect Of Mixed Juice Of Young Green Coconut And Date Fruits On The Duration Of Active Phase Of Labor - Yuli Astuti; Is Susiloningtyas (Jurnal Kebidanan dan Kesehatan Tradisional, 2021)
Background: The delivery process need a lot of energy from food. Juice preparation is one of the recommended food forms during labor. This study was purposed to analyze the effect of giving mixed juices of young green coconut and dates on the duration of the active phase of the first stage of labor. Methods: A quasi-experiment with a post-test only with control group design include 18 pregnant women (10 intervention and 8 control. Purposive sampling was used, respondents were multigravida (P2-P4) in active phase of labor, without previous section caesarean, no augmentation with oxytocin, estimated birth weight was 2500-4000 gr, singleton pregnancy, aterm labor, and without any other complication during delivery at Alian Public Health Center, Kebumen Regency in October - December 2020. The intervention group given 500 mL of mixed juice of young green coconut and dates during the first stage of labor and control group received standard care. Mann-Whitney test was used to analyze median difference between two groups. Results: There was no difference in the duration of the active phase of the first stage of labor between the intervention and control group (P-value 0,756). There was no difference of the rate of cervix dilatation between the two groups (P-value 0,408). The median of the active phase of the first stage of labor was 197,5 minutes and 147,5 minutes respectively. The median of rate cervix dilatation in the intervention group was 1,96 cm per hour and 1,94 cm per hour respectively. The rate of cervix dilatation in both groups was in normal category. Respondent in standard group was not forbidden eating and drinking, so both groups received enough energy and hydration during labor. Conclusion: Mixed juice of young green coconut and dates can be given during labor to fulfill the energy need during labor.